2015
DOI: 10.1159/000431227
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Levels in the Hair of Different Cattle Breeds

Abstract: Background: Cattle are well-known sources of respiratory allergens in agricultural environments. Breed-specific differences in Bos d 2 (a major bovine allergen) levels in cattle hair have been previously suggested but not fully characterized. Therefore, the aim of the current study was to determine whether hair from common cattle breeds differs in protein and allergen content. Methods: In total, 80 hair samples from 16 different cattle breeds were analyzed. The protein concentration was determined using the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Allergen levels of Fel d 1, Can f 1, and Bos d 2 were determined using monoclonal antibodies and calibration standards purchased from Indoor Biotechnologies Inc. (Charlottesville, VA, USA) according to protocols described previously for cat and dog ( Sander and Lotz et al , 2016 ) and for cattle ( Zahradnik et al , 2015 ). Equ c 1 concentrations were quantified using an immunoassay based on polyclonal antibodies and naturally-purified Equ c 1 as a standard ( Zahradnik et al , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Allergen levels of Fel d 1, Can f 1, and Bos d 2 were determined using monoclonal antibodies and calibration standards purchased from Indoor Biotechnologies Inc. (Charlottesville, VA, USA) according to protocols described previously for cat and dog ( Sander and Lotz et al , 2016 ) and for cattle ( Zahradnik et al , 2015 ). Equ c 1 concentrations were quantified using an immunoassay based on polyclonal antibodies and naturally-purified Equ c 1 as a standard ( Zahradnik et al , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…A study performed in Germany on the most common cattle breeds showed a high variability in allergen levels between individual animals. The results also indicated that allergen production was not related to breed or to gender . Similar studies have been performed for horses and, for example, the Bashkir horse and the American Curly horse have been suggested to be hypoallergenic .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, allergen loads shed by an individual animal can vary enormously. Variations in allergen content of hair up to four orders of magnitude were observed in dogs 22) , horses 13,23) , and cattle 24) of different breeds and sexes. Another factor that could influence the high variability of allergen levels was talking during dust collection, which was not restricted as in other studies 8) .…”
Section: Ofmentioning
confidence: 99%